Psychological Adjustment tsunami affected children and adolescents - Senerath, S. (My University, 2007)
This study investigated the long-term psychosocial effects after the three years of tsunami exposure, i.e. post-traumatic stress disorder (PTSD), anxiety, and educational and social relationship difficulties. To facilitate psychological well-being, two types of interventions were implemented. 1. A mediator intervention for children (MIC) with autoregulative treatment approach and 2. A mediator training program for counselors (MTPC) conducted by professionals in psychology for those who became mediators (counselors) for treatment towards affected children and adolescents. A quasi-experimental design of two groups pretest and posttest was conducted to assess the children’s intervention. Data were collected from 80 children and adolescents being affected by the tsunami, with n=40 in the experimental group (EG) and n=40 in the control group (CG) using standardized tests, i.e. Childhood Post-traumatic Stress Reaction Index (CPTS-RI), the Revised Children’s Manifest Anxiety Scale (RCMAS), and a self-developed questionnaire for the educational and social relationships difficulties. For the MTPC, a one–group pretest and posttest design was applied. Data were collected by using a self-developed knowledge based screening test from 20 counselors. All participants were from Matara District in Southern Sri Lanka. Prior intervention results (pretest) proved that children encountered mild-to severe PTSD symptoms. The two-way ANOVAs with three measurement times stated that there was overall reduction of PTSD, anxiety, and educational and social relationships difficulties of the EG compared to the CG. And also the experimental group children’s emotions are changed towards negative to positive aspects. Through the mediator training program, counselors’ knowledge significantly increased in comparison to the pretest.